PELATIHAN MANAJEMEN ORGANISASI DAN KADERISASI SERTA IMPLEMENTASI PENDIDIKAN POLITIK DALAM ORGANISASI KEMAHASISWAAN (ORMAWA) - Asep Munajat; Ibnu Hurri; Leonita Siwiyanti (LPPM IKIP Jember, 2018)
This article discusses the importance of organizational management at ORMAWA at the Muhammadiyah University of Sukabumi, where the knowledge of the students about the organization is still primordial, meaning that organizational knowledge is obtained from older siblings so that organizational knowledge is still static. Knowledge of trial mechanisms and procedures for amendments to AD / ART are not fully understood. This leads to low understanding of students about organizational management and regeneration and implementation of political education in student organizations (ORMAWA). The Science and Technology Program for the Society (IbM) conducted at the Muhammadiyah University of Sukabumi is targeted at the second and third year students who are the board of ORMAWA, consisting of 20 HIMA, 5 BEM Faculty, 1 BEM University, 1 DPM University, and 1 DPM Faculty, giving new colors / understanding about ORMAWA. In an effort to improve the quality of student organizations within the campus, continuous training on the understanding of good organizational management is required. The result of this activity are: (1) Creation of ORMAWA organizers who understand and able to implement organizational management and regeneration and implementation of political education in student organizations (ORMAWA), (2) The formation of students who are able to think critically in problem solving.